Performance Evaluation of a Small-Scale Turbojet Engine Running on Palm Oil Biodiesel Blends. (8th July 2014) - Abu Talib, A. R.; Gires, E.; Ahmad, M. T.
Abstract : The experimental and simulated performance of an Armfield CM4 turbojet engine was investigated for palm oil methyl ester biodiesel (PME) and its blends with conventional Jet A-1 fuel. The volumetric blends of PME with Jet A-1 are 20, 50, 70, and 100% (B20, B50, B70, and B100). Fuel heating values (FHV) of each fuel mixture were obtained by calorimetric analysis. The experimental tests included performance tests for Jet A-1 and B20, while the performances of B50 to B100 were simulated using GasTurb 11 analytical software. In terms of maximum measured thrust, Jet A-1 yielded the highest value of 216 N, decreasing by 0.77%, 4%, 8%, and 12% with B20, B50, B70, and B100. It was found that B20 produced comparable results compared to the benchmark Jet A-1 tests, particularly with thrust and thermal efficiency. Slight performance penalties occurred due to the lower energy content of the biodiesel blends. The efficiency of the combustor improved with the addition of biodiesel while the other component efficiencies remained collectively consistent. This research shows that, at least for larger gas turbines, PME is suitable for use as an additive to Jet A-1 within 50% blends.